Tunable lasers handbook - Duarte, F. J. (Frank J.) (Optics and photonics., 1995)
Many laser applications depend on the ability of a particular laser to be frequency tunable. Among the many different types of frequency tunable lasers are: dye lasers, excimer lasers, and semiconductor lasers. Thisbook gives active researchers and engineers the practical information they need to choose an appropriate tunable laser for their particular applications. Key Features * Presents a unified and integrated perspective on tunable lasers * Includes sources spanning the electromagnetic spectrum from the UV to the FIR * Contains 182 figures and 68 tables * Provides coverage of optical parametric oscillators and tunable gas, liquid, solid state, and semiconductor lasers.